Two-step pulse-shrinking time-to-digital converter. (February 2017) - Park, Young Jun; Yuan, Fei
Abstract: This paper presents a two-step pulse-shrinking time-to-digital converter (TDC) consisting of a 4-stage coarse pulse-shrinking TDC with per-stage shrinkage 1 ns and a 4-stage fine pulse-shrinking TDC with per-stage shrinkage 250 ps. A simple residual time extraction scheme is proposed to extract the residual pulse of the coarse TDC. The characteristics of the TDC including mismatch and noise-induced timing errors, timing errors of delay blocks, conversion time, power consumption, and silicon consumption are analyzed in detail. The proposed TDC was implemented in an IBM 130 nm 1.2 V CMOS technology. Simulation results show that the proposed TDC offers 1.4 ns conversion time, 1 LSB DNL and INL, and figure-of-merit (FoM) of 0.163 pJ/step. Some measurement results of the proposed TDC are also presented.